HISTORY AND POLITICS OF CURRENCY CHANGES IN NIGERIA UP TO 2008 - SHINA ALIMI; ABIMBOLA ADESOJI (International Studies Journal)
Whether from the pound sterling to the naira or from lower to higher denominations or even from one colour to another, Nigerian currency has gone through changes at different times in its history. Obviously, a product of the prevailing political situations and socio-economic realities, its social implications on Nigerians are tremendous. This paper examines the history and the politics of currency changes in Nigeria up to 2008. The paper explores different policies and programs formulated at different times to stabilize the naira, and accounts for how the prevailing national and global economic conditions strengthened or weakened the currency. The paper argues that beyond serving as a means of exchange, the naira symbolizes the Nigerian national identity, pride and unity, as well marks the state sovereignty.